Randomized Controlled Trial of Group Exercise Intervention for Fall Risk Factors Reduction in Nursing Home Residents. Issue 2 (11th June 2023) - Pepera, Garyfallia; Krinta, Katerina; Mpea, Christina; Antoniou, Varsamo; Peristeropoulos, Argirios; Dimitriadis, Zacharias
Abstract: Objective: The aim of this study was to assess the effectiveness of a multidimensional exercise intervention on improving fall risk deterrent factors, such as overall strength and flexibility in nursing home residents. Methods: A multi-centre, randomized controlled trial was finally utilized in 40 older adults (>65 years) who were randomly allocated to the intervention or the control group (20 subjects in each). The intervention group attended an exercise program twice a week for eight weeks, to improve functional mobility. The control group did not receive any intervention. Measurements before and after intervention included the Hand Grip Strength (HGS) testing, the Sit-to-Stand test (SST), the Back Scratch Test (BST), and the Sit-and-Reach test (SRT). Results: MANOVA revealed significant time effects, V = 0.336, F (6, 33) = 2.78, p = 0.027, partial η 2 = 0.336; group effects, V = 0.599, F (6, 33) = 8.22, p < 0.001, partial η 2 = 0.599; and group*time interaction, V = 0.908, F (6, 33) = 54.52, p < 0.001, partial η 2 = 0.908. A subsequent univariate analysis did not reveal a significant time effect for any variable ( p > 0.05). Significant group effects were observed only for SRT ( p < 0.05). Significant group*time interactions were observed for all the examined variables ( p < 0.05). Dependent t-tests showed that the older adults in the exercise group were significantly improved in all the examined parameters ( p < 0.05). Except for SRT ( p > 0.05), all the other parameters significantly deteriorated in the control group ( p < 0.05). Conclusions: Significant improvements were demonstrated in strength and flexibility among nursing home residents following an eight-week group exercise training program.